Comparing the Efficacy of Bupropion and Amantadine on Sexual Dysfunction Induced by a Selective Serotonin Reuptake Inhibitor - Zahiroddin, Alireza (Iran Red Crescent Med J, 2015)
BACKGROUND: Antidepressant-induced sexual dysfunction (SD) is a common problem, associated with a significant risk of non-adherence. Selective Serotonin Reuptake Inhibitors (SSRIs) are associated with a substantial risk of SD. Only 10 % of patients show spontaneous improvement during follow up period. OBJECTIVES: This study aimed to compare two proposed medication (bupropion vs. amantadine) in alleviating SD in patients treated with SSRIs. PATIENTS AND METHODS: In a randomized, single-blinded, clinical trial in Iran, 46 patients were recruited based on DSM-IV-TR criteria and semi-structured interview. Then, they were randomized into two treatment groups using table of random numbers. Eight patients were excluded and finally 38 patients completed the study which lasted for 4 weeks. Twenty patients were given bupropion, 18 patients were randomly assigned to another group, and given amantadine. Patients were assessed with the Arizona sexual experience scale (ASEX) at baseline and 4 weeks after the treatment. RESULTS: A total of 38 patients completed the study (18 patients in amantadine vs. 20 patients in bupropion).The mean ASEX scores gradually declined in both study groups during the trial. The reduction of ASEX score in bupropion group was more than that of amantadine group that was statistically significant. So, the addition of bupropion at higher doses appears to be more effective approach in comparison with amantadine. CONCLUSIONS: These results provide empirical support for conducting a further study on comparing different add-on strategies for treating drug-induced SD.